Effectiveness of a preoperative explanatory video system on patient acceptance and anesthesiologists’ workload: a questionnaire survey - Kohei Akemoto; Kotoe Kamata; Yu Kaiho; Eiko Onishi; Shizuha Yabuki; Takuya Shiga; Masanori Yamauchi (JA Clinical Reports)
Abstract Background High-quality preoperative patient education is crucial for enhancing comprehension and reducing anxiety. However, anesthesiologists often face time constraints that limit the depth of preoperative consultations. To address this challenge, we implemented a tablet-based preanesthetic explanatory video preview system, allowing patients to view tailored video clips prior to their consultation. This study aimed to evaluate the system’s impact on patient acceptance and the workload of anesthesiologists. Methods A questionnaire-based survey was conducted at our outpatient clinic between October 27 and November 20, 2023. A total of 121 patients and 20 anesthesiologists participated. Patients completed a three-point scale questionnaire assessing the video’s clarity, relevance, and overall satisfaction. Anesthesiologists provided feedback on the efficiency of consultations and workload. Results Ninety-five percent of patients found the video “easy to understand,” and 96% expressed overall satisfaction. Thirteen out of 14 anesthesiologists reported that the video improved patient understanding and reduced consultation time, with an average time savings of 3.9 ± 3.2 min per patient. None reported an increase in workload. Conclusions The preanesthetic video preview system improved patient comprehension and satisfaction while enhancing consultation efficiency. Standardizing preoperative education through video may optimize clinical workflow and reduce the burden on anesthesiologists. Further research is warranted to assess its applicability across diverse patient populations and surgical settings.